Relationship between diet, oxidative stress, and inflammation in ankylosing spondylitis - Kübra Tel Adıgüzel,; Fatma Gül Yurdakul,; Nilgün Seremet Kürklü,; Evren Yaşar,; Hatice Bodur, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the relationship between disease activity, dietary phytochemical index (DPI), and serum total oxidant status (TOS) and total antioxidant status (TAS) in patients with ankylosing spondylitis (AS). Patients and methods: Between August 2020 and January 2021, a total of 37 patients (23 males, 14 females; mean age: 39.3±9.4 years; range, 21 to 61 years) with AS and 36 age-, sex-, and body mass index-matched healthy individuals (24 males, 12 females; mean age: 37.9±8.9 years; range, 20 to 60 years) were included. Serum TAS (μmoLTroloxEq/L) and TOS (μmoL H2O2Eq/L) measurements were performed and the oxidative stress index (OSI) was calculated. Dietary evaluation was made from a one-day dietary record and DPI was calculated. Results: Serum TAS level in AS patients was significantly lower than the healthy group (p=0.003). Serum TOS level was similar in both groups. The OSI of patients was significantly higher than the controls (p=0.035). The mean DPI, polyunsaturated fatty acid, n-3 fatty acid, and vitamin C intake of patients were significantly lower than controls (p=0.042, p=0.033, and p=0.022, respectively). A moderate positive correlation was found between the TAS level and DPI of the control group (r=0.352, p=0.035). According to medications, no significant difference was seen between the groups in terms of patients’ characteristics, DPI, and laboratory tests and there was no correlation between DPI, TAS, TOS, and OSI. Conclusion: Lower DPI and lower n-3 fatty acid and vitamin C intake in patient group demonstrated that patients with AS should pay more attention to their diet to increase serum antioxidant status.